2019
DOI: 10.1038/s41598-019-46859-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards prognostic functional brain biomarkers for cervical myelopathy: A resting-state fMRI study

Abstract: Recently, there has been increasing interest in strategies to predict neurological recovery in cervical myelopathy (CM) based on clinical images of the cervical spine. In this study, we aimed to explore potential preoperative brain biomarkers that can predict postoperative neurological recovery in CM patients by using resting-state functional magnetic resonance imaging (rs-fMRI) and functional connectivity (FC) analysis. Twenty-eight patients with CM and 28 age- and sex-matched healthy controls (HCs) underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 37 publications
1
38
0
1
Order By: Relevance
“…Moreover, the effects we observed for the increased FC in CSM patients may seem surprising at the first glance. However, this phenomenon (i.e., increased FC and increased network efficiency in CSM patients) has been continually reported in numerous neuroimaging studies of CSM (4,10,26,70). These studies continuously reported increased FC in CSM patients, and this phenomenon has been interpreted as a compensatory or adaptive change due to abnormal ascending or descending signal caused by long-term spinal compression.…”
Section: Increased Functional Connectivity and Dmn Global Efficiency mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the effects we observed for the increased FC in CSM patients may seem surprising at the first glance. However, this phenomenon (i.e., increased FC and increased network efficiency in CSM patients) has been continually reported in numerous neuroimaging studies of CSM (4,10,26,70). These studies continuously reported increased FC in CSM patients, and this phenomenon has been interpreted as a compensatory or adaptive change due to abnormal ascending or descending signal caused by long-term spinal compression.…”
Section: Increased Functional Connectivity and Dmn Global Efficiency mentioning
confidence: 99%
“…However, emerging evidence suggest that cortical alterations may also be crucial in CSM pathology (4)(5)(6)(7). It has been shown that the cortical alterations can only partly restore after decompression surgery (8,9), and the preoperative neural activities can be used as a potential biomarker to predict surgical outcomes (10). To investigate functional alteration at the brain level in CSM patients, functional magnetic resonance imaging (fMRI), which is a highly effective method for investigating neurological and psychological conditions, has been widely applied (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous neuroimaging studies have demonstrated that CSM patients display altered neural activity in the superior frontal gyrus. Takenaka et al observed significantly high functional connectivity between superior frontal and lingue gyrus in (healthy individuals), and surgery substantially improved this phenomenon in CSM patients ( 66 ). In their subsequent study using the same cohort, Takenaka et al found that decompression surgery increased ALFF in the superior frontal gyrus of CSM patients ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although we observed a significant across-voxel correlation between rCBF and FCS in CSM patients, it was substantially lower than that of healthy patients, implying decoupling between rCBF and FCS in CSM patients. This neurovascular decoupling may have resulted from prolonged neuroinflammation caused by myelopathy (61)(62)(63), in which the abnormally functioning astrocytes in CSM patients may have reduced the regional neural activity and blood supply (62,64,65). Neuroinflammation would have also directly affected the vascular component, leading to neurovascular decoupling in CSM patients.…”
Section: Discussionmentioning
confidence: 99%